High-solid-content slurry, preparation method thereof and lithium ion battery
By using cationic dispersant in the semi-dry kneading process, the solid content and stability of the positive electrode slurry are improved, the problem of increasing the solid content is solved, production costs are reduced, and battery performance is not affected.
Patent Information
- Application Number
- CN202411879371.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
How to effectively increase the solid content of the positive electrode slurry through the semi-dry kneading process without affecting the performance of the existing battery and reduce production costs.
By mixing the conductive agent, the positive electrode active material, the dispersant and the solvent, a slurry of slightly higher viscosity is obtained and mixed with the binder solution to form a slurry of high solids. Use a cationic dispersant to adjust the solids and viscosity of the slurry.
It improves the solid content and stability of the positive electrode slurry, reduces production costs, does not affect the performance of the battery, and enhances the market competitiveness of the battery.
Smart Images

Figure BDA0005197797480000131 
Figure BDA0005197797480000132 
Figure BDA0005197797480000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a high-solid content slurry and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Under the background of "carbon neutrality" and "carbon peak", the development and utilization of new energy sources are on the agenda, and are accelerating under the dual drive of policies and markets. Electrochemical energy storage includes the energy storage needs of communication energy storage and wind and solar power generation. Among them, communication energy storage is divided into the energy storage needs of newly built 5G base stations and the battery replacement needs of 4G base stations.
[0003] As the energy storage market becomes increasingly prosperous, energy storage battery products are developing towards large capacity. According to measured data, large-capacity lithium-ion cells can greatly improve the energy density of energy storage systems, and are one of the important trends in system development choices (currently mainly referring to 280Ah large cells). Compared with 50 and 100Ah products, large-capacity 280Ah and above batteries have higher volume energy density and use fewer PACK-end components, which can greatly save cost investment. With the price fluctuations of raw materials such as lithium ore, the cost advantage is obvious. In terms of production and manufacturing, the increase in capacity can effectively simplify the subsequent integration and assembly process, saving equipment, energy consumption and manpower.
[0004] From the demand side, 280Ah large-capacity lithium-ion batteries have a high penetration rate in large-scale energy storage power stations. Owners and investors of large-scale energy storage power stations are paying more and more attention to 280Ah large-capacity batteries. Owners such as China Energy Engineering and China Huadian Huadian have explicitly required battery cells with a capacity of 280Ah or above in energy storage battery bidding.
[0005] From the supply side, since CATL launched the 280Ah battery cell in 2019, more than 10 leading energy storage companies in China have deployed large-capacity energy storage battery cell products.
[0006] Chinese patent CN107834019A discloses a method for preparing battery slurry with high solid content. The method for preparing battery slurry in this method is a wet preparation process. In actual production, the wet process is easier to increase the solid content of slurry than the semi-dry process, and the cost saving is slightly lower than the semi-dry process. However, in terms of the semi-dry production process, the effective increase of the solid content of the positive electrode slurry has not been properly solved.
[0007] In summary, how to effectively increase the solid content of the semi-dry kneading process slurry and effectively reduce the production cost without affecting the performance of existing batteries is an urgent problem that technicians in this field need to solve. Summary of the invention
[0008] In view of this, the technical problem to be solved by the present invention is to provide a high-solid content slurry and a preparation method thereof and a lithium-ion battery. The preparation method of the high-solid content slurry provided by the present invention can effectively increase the solid content of the semi-dry kneading process slurry without affecting the battery performance.
[0009] The present invention provides a method for preparing a high-solid content slurry, comprising the following steps:
[0010] A) mixing a conductive agent, a positive electrode active material, a dispersant and a solvent to obtain a slightly high viscosity slurry, wherein the dispersant is selected from a cationic dispersant;
[0011] B) mixing the binder with the solvent to obtain a mixed glue solution;
[0012] C) mixing the slightly higher viscosity slurry with the mixed glue to obtain a high solid content slurry.
[0013] The present invention also provides a method for preparing a high solid content slurry, comprising the following steps:
[0014] a) mixing a positive electrode active material, a dispersant and a solvent and then mixing with a conductive agent slurry to obtain a slightly higher viscosity slurry, wherein the dispersant is selected from a cationic dispersant;
[0015] b) mixing the binder with the solvent to obtain a mixed glue solution;
[0016] c) mixing the slightly higher viscosity slurry with the mixed glue to obtain a slurry with a high solid content.
[0017] The present invention also provides a method for preparing a high solid content slurry, comprising the following steps:
[0018] 1) mixing a conductive agent, a positive electrode active material, a dispersant and a solvent and then mixing with a conductive agent slurry to obtain a slightly higher viscosity slurry, wherein the dispersant is selected from a cationic dispersant;
[0019] 2) mixing the binder and the solvent to obtain a mixed glue solution;
[0020] 3) Mixing the slightly higher viscosity slurry with the mixed glue to obtain a high solid content slurry.
[0021] Preferably, the mass percentage of the cationic dispersant in the high solid content slurry is 0.3% to 0.5%;
[0022] The cationic dispersant is selected from amine salt dispersants.
[0023] Preferably, the amine salt dispersant is selected from one or more of an alcohol amine dispersant, a quaternary ammonium salt dispersant, and a pyridinium salt dispersant.
[0024] Preferably, step A) comprises:
[0025] A1) dry-mixing the conductive agent with part of the positive electrode active material to obtain a mixed powder;
[0026] Dispersing and wetting the mixed powder with a solvent and kneading them to obtain a slurry mass;
[0027] A2) mixing the dispersant, the solvent and the remaining positive electrode active material with the slurry mass to obtain a slurry with a slightly higher viscosity;
[0028] Step a) comprises:
[0029] a1) dispersing and wetting a portion of the positive electrode active material with a solvent and kneading the mixture to obtain a slurry mass;
[0030] a2) mixing the dispersant, the solvent and the remaining positive electrode active material with the slurry mass, and then mixing with the conductive agent slurry for pre-stirring and high-speed dispersion to obtain a slurry with slightly higher viscosity;
[0031] Step 1) includes:
[0032] 1-1) dry-mixing the conductive agent with part of the positive electrode active material to obtain a mixed powder;
[0033] Dispersing and wetting the mixed powder with a solvent and kneading them to obtain a slurry mass;
[0034] 1-2) The dispersant, the solvent and the remaining positive electrode active material are mixed with the slurry mass and stirred, and then mixed with the conductive agent slurry for pre-stirring and high-speed dispersion to obtain a slurry with slightly higher viscosity.
[0035] Preferably, in step A1) and step 1-1), the dry mixing time is 30±5 min, and the speed is: revolution 25-30 rpm, dispersion 1500-1600 rpm;
[0036] In step A1) and step 1-1), the order of adding materials in the dry mixing is half the mass of part of the positive electrode active material, the conductive agent and the other half the mass of part of the positive electrode active material;
[0037] In step A1), step a1) and step 1-1), the revolution speed of the kneading step is 15 to 20 rpm;
[0038] In step A2), step a2) and step 1-2), the mixing and stirring time is 90 to 100 minutes, the speed is 25 to 30 rpm for revolution, 800 to 900 rpm for dispersion, and the temperature is controlled at 44 to 46°C;
[0039] In step a2) and step 1-2), the pre-stirring time is 10 to 15 minutes, the speed is 15 to 20 rpm for revolution and 500 to 600 rpm for dispersion; the high-speed dispersion time is 60 to 65 minutes, the speed is 30 to 35 rpm for revolution and 3000 to 3500 rpm for dispersion;
[0040] In step C), step c) and step 3), the mixing includes pre-stirring and high-speed dispersion, the pre-stirring time is 10 to 15 minutes, the speed is 15 to 20 rpm for revolution and 500 to 600 rpm for dispersion; the high-speed dispersion time is 90 to 100 minutes, the speed is 30 to 35 rpm for revolution and 3200 ± 10 rpm for dispersion, and the temperature is controlled at 34 to 36°C.
[0041] Preferably, in the mixed glue, the mass ratio of the binder to the solvent is (5% to 10%): (95% to 90%);
[0042] In the high solid content slurry of step C), the mass ratio of the positive electrode active material, the binder, and the conductive agent is (95.8-96.3%): (1.8-2.2%): (0.8-1.2%);
[0043] In the high solid content slurry of step c), the mass ratio of the positive electrode active material, the binder and the conductive slurry is (95.8-96.3%): (1.8-2.2%): (0.7-1.0%);
[0044] In the high solid content slurry of step 3), the mass ratio of the positive electrode active material, the binder, the conductive agent and the conductive slurry is (95.8-96.3%): (1.8-2.2%): (0.8-1.2%): (0.7-1.0%);
[0045] In step A1), step a1) and step 1-1), the mass ratio of part of the positive electrode active material to the remaining part of the positive electrode active material is 50-60:40-50.
[0046] The present invention also provides a high-solid content slurry prepared by the above preparation method.
[0047] The present invention also provides a lithium ion battery, comprising the above-mentioned high solid content slurry.
[0048] Compared with the prior art, the present invention provides a method for preparing a high-solid content slurry, comprising the following steps: A) mixing a conductive agent, a positive electrode active material, a dispersant and a solvent to obtain a slightly high-viscosity slurry, wherein the dispersant is selected from a cationic dispersant; B) mixing a binder with a solvent to obtain a mixed glue solution; C) mixing the slightly high-viscosity slurry with the mixed glue solution to obtain a high-solid content slurry. The method for preparing a high-solid content slurry by a semi-dry kneading process for lithium-ion batteries provided by the present invention does not change the original semi-dry kneading process, and through the correct use of a cationic dispersant, improves the solid content and stability of the positive electrode slurry, reduces production costs, and further enhances the market competitiveness of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 The process flow chart of preparing the high solid content slurry by the semi-dry kneading process provided in Examples 1 and 2;
[0050] Figure 2 The process flow chart of the positive electrode slurry prepared in Comparative Example 1;
[0051] Figure 3 The graphs are the changes of the viscosity of the slurries prepared in Example 1 and Comparative Example 1 over time;
[0052] Figure 4 This is a test result diagram of a 2C rate discharge platform of a full battery prepared with the positive electrode slurries of Example 1 and Comparative Example 1 at 25°C;
[0053] Figure 5 This is a graph showing the test results of a full battery prepared with the positive electrode slurries of Example 1 and Comparative Example 1 at 25°C and 0.5C / 0.5C charge and discharge cycle. DETAILED DESCRIPTION
[0054] The present invention provides a method for preparing a high-solid content slurry, wherein, according to the requirements of the conductive performance, a conductive agent (solid) or a conductive agent slurry can be used alone, or a conductive agent (solid) and a conductive agent slurry can be used simultaneously. Therefore, according to different types of conductive agents, the present invention provides three methods for preparing a high-solid content slurry.
[0055] Wherein, when the conductive agent (solid) is used alone, the preparation method of the high solid content slurry comprises the following steps:
[0056] A) mixing a conductive agent, a positive electrode active material, a dispersant and a solvent to obtain a slightly high viscosity slurry, wherein the dispersant is selected from a cationic dispersant;
[0057] B) mixing the binder with the solvent to obtain a mixed glue solution;
[0058] C) mixing the slightly higher viscosity slurry with the mixed glue to obtain a high solid content slurry.
[0059] Specifically, step A) includes:
[0060] A1) dry-mixing the conductive agent with part of the positive electrode active material to obtain a mixed powder;
[0061] Dispersing and wetting the mixed powder with a solvent and kneading them to obtain a slurry mass;
[0062] A2) mixing the dispersant, the solvent and the remaining positive electrode active material with the slurry mass to obtain a slurry with a slightly higher viscosity;
[0063] The present invention firstly dry-mixes the conductive agent with part of the positive electrode active material to obtain a mixed powder.
[0064] The present invention has no special restrictions on the type of the conductive agent, preferably, it can be one or more of conductive carbon black, carbon nanotubes, and graphene. The present invention has no special restrictions on the specific type of the positive electrode active material, and the positive electrode active material known to those skilled in the art can be used. The dry mixing time is 30±5min, and the speed is: revolution 25-30rpm, dispersion 1500-1600rpm.
[0065] In some specific embodiments of the present invention, the order of adding materials in the dry mixing is half the mass of part of the positive electrode active material, the conductive agent and the other half the mass of part of the positive electrode active material.
[0066] The mixed powder is dispersed and wetted with a solvent and kneaded to obtain a slurry mass. The revolution speed of the kneading step is 15 to 20 rpm. The present invention does not specifically limit the type of solvent used to prepare the slurry, and any solvent known to those skilled in the art for preparing battery slurry can be used. In the present invention, N-methylpyrrolidone (NMP) is preferably used.
[0067] The dispersant, the solvent and the remaining positive electrode active material are mixed with the slurry mass and stirred to obtain a slightly high viscosity slurry. In the present invention, the dispersant is selected from a cationic dispersant, preferably, the cationic dispersant is selected from an amine salt dispersant, and more preferably, the amine salt dispersant is selected from one or more of an alcoholamine dispersant, a quaternary ammonium salt dispersant, and a pyridinium salt dispersant.
[0068] In the present invention, the mass percentage of the cationic dispersant in the high solid content slurry is 0.3% to 0.5%, which can be 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, or any value between 0.3% and 0.5%.
[0069] The mixing and stirring time is 90 to 100 minutes, the speed is 25 to 30 rpm for revolution, 800 to 900 rpm for dispersion, and the temperature is controlled at 44 to 46° C. In the present invention, the mass ratio of part of the positive electrode active material to the remaining part of the positive electrode active material is 50 to 60:40 to 50, which can be 50:50, 55:45, 60:40, or any value between 50 to 60:40 to 50.
[0070] The present invention also mixes a binder with a solvent to obtain a mixed glue solution; in the mixed glue solution, the mass ratio of the binder to the solvent is (5% to 10%): (95% to 90%), which can be any value between 5%: 95%, 7%: 93%, 10%: 90%, or (5% to 10%): (95% to 90%). In the present invention, there is no special restriction on the type of the bonding, and any type of binder known to those skilled in the art can be used. In the present invention, the binder is preferably polyvinylidene fluoride.
[0071] Finally, the slightly high viscosity slurry is mixed with the mixed glue to obtain a high solid content slurry. The mixing includes pre-stirring and high-speed dispersion, the pre-stirring time is 10-15 minutes, the speed is 15-20 rpm for revolution and 500-600 rpm for dispersion; the high-speed dispersion time is 90-100 minutes, the speed is 30-35 rpm for revolution and 3200±10 rpm for dispersion, and the temperature is controlled at 34-36°C.
[0072] In the high solid content slurry, the mass ratio of the positive electrode active material, the binder and the conductive agent is (95.8-96.3%): (1.8-2.2%): (0.8-1.2%).
[0073] Wherein, when the conductive agent slurry is used alone, the preparation method of the high solid content slurry comprises the following steps:
[0074] a) mixing a positive electrode active material, a dispersant and a solvent and then mixing with a conductive agent slurry to obtain a slightly higher viscosity slurry, wherein the dispersant is selected from a cationic dispersant;
[0075] b) mixing the binder with the solvent to obtain a mixed glue solution;
[0076] c) mixing the slightly higher viscosity slurry with the mixed glue to obtain a slurry with a high solid content.
[0077] Specifically, step a) includes:
[0078] a1) dispersing and wetting a portion of the positive electrode active material with a solvent and kneading the mixture to obtain a slurry mass;
[0079] a2) The dispersant, the solvent and the remaining positive electrode active material are mixed with the slurry mass and stirred, and then mixed with the conductive agent slurry for pre-stirring and high-speed dispersion to obtain a slurry with slightly higher viscosity.
[0080] The present invention firstly disperses and wets a part of the positive electrode active material with a solvent and kneads them to obtain a slurry mass. The revolution speed of the kneading step is 15 to 20 rpm. The present invention has no special restrictions on the type of solvent used to prepare the slurry, and any solvent known to those skilled in the art for preparing battery slurry can be used. In the present invention, NMP is preferably used. The present invention has no special restrictions on the specific type of the positive electrode active material, and any positive electrode active material known to those skilled in the art can be used.
[0081] The dispersant, the solvent and the remaining part of the positive electrode active material are mixed with the slurry mass and stirred. In the present invention, the dispersant is selected from a cationic dispersant, preferably, the cationic dispersant is selected from an amine salt dispersant, and further preferably, the amine salt dispersant is selected from one or more of an alcoholamine dispersant, a quaternary ammonium salt dispersant, and a pyridinium salt dispersant.
[0082] In the present invention, the mass percentage of the cationic dispersant in the high solid content slurry is 0.3% to 0.5%, which can be 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, or any value between 0.3% and 0.5%.
[0083] The mixing and stirring time is 90 to 100 minutes, the speed is 25 to 30 rpm for revolution, 800 to 900 rpm for dispersion, and the temperature is controlled at 44 to 46° C. In the present invention, the mass ratio of part of the positive electrode active material to the remaining part of the positive electrode active material is 50 to 60:40 to 50, which can be 50:50, 55:45, 60:40, or any value between 50 to 60:40 to 50.
[0084] Then, it is mixed with the conductive agent slurry for pre-stirring and high-speed dispersion to obtain a slightly higher viscosity slurry. The pre-stirring time is 10 to 15 minutes, the speed is 15 to 20 rpm for revolution and 500 to 600 rpm for dispersion; the high-speed dispersion time is 60 to 65 minutes, the speed is 30 to 35 rpm for revolution and 3000 to 3500 rpm for dispersion; the present invention has no special restrictions on the conductive slurry, and any conductive slurry known to those skilled in the art can be used. In the present invention, the conductive slurry is preferably a conductive graphite slurry or a carbon nanotube slurry.
[0085] The present invention also mixes a binder with a solvent to obtain a mixed glue solution; in the mixed glue solution, the mass ratio of the binder to the solvent is (5% to 10%): (95% to 90%), which can be any value between 5%: 95%, 7%: 93%, 10%: 90%, or (5% to 10%): (95% to 90%). In the present invention, there is no special restriction on the type of the bonding, and any type of binder known to those skilled in the art can be used. In the present invention, the binder is preferably polyvinylidene fluoride.
[0086] Finally, the slightly high viscosity slurry is mixed with the mixed glue to obtain a high solid content slurry. The mixing includes pre-stirring and high-speed dispersion, the pre-stirring time is 10-15 minutes, the speed is 15-20 rpm for revolution and 500-600 rpm for dispersion; the high-speed dispersion time is 90-100 minutes, the speed is 30-35 rpm for revolution and 3200±10 rpm for dispersion, and the temperature is controlled at 34-36°C.
[0087] In the high solid content slurry, the mass ratio of the positive electrode active material, the binder and the conductive slurry is (95.8-96.3%): (1.8-2.2%): (0.7-1.0%).
[0088] When the conductive performance is required to be high, a conductive agent (solid) and a conductive agent slurry can be used simultaneously. The preparation method of the high solid content slurry comprises the following steps:
[0089] 1) mixing a conductive agent, a positive electrode active material, a dispersant and a solvent and then mixing with a conductive agent slurry to obtain a slightly higher viscosity slurry, wherein the dispersant is selected from a cationic dispersant;
[0090] 2) mixing the binder and the solvent to obtain a mixed glue solution;
[0091] 3) Mixing the slightly higher viscosity slurry with the mixed glue to obtain a high solid content slurry.
[0092] Wherein, step 1) comprises:
[0093] 1-1) dry-mixing the conductive agent with part of the positive electrode active material to obtain a mixed powder;
[0094] Dispersing and wetting the mixed powder with a solvent and kneading them to obtain a slurry mass;
[0095] 1-2) The dispersant, the solvent and the remaining positive electrode active material are mixed with the slurry mass and stirred, and then mixed with the conductive agent slurry for pre-stirring and high-speed dispersion to obtain a slurry with slightly higher viscosity.
[0096] The present invention firstly dry-mixes the conductive agent with part of the positive electrode active material to obtain a mixed powder.
[0097] The present invention has no special restrictions on the type of the conductive agent, preferably, it can be conductive carbon black, carbon nanotubes, graphene, etc. The present invention has no special restrictions on the specific type of the positive electrode active material, and the positive electrode active material known to those skilled in the art can be used. The dry mixing time is 30±5min, and the speed is: revolution 25-30rpm, dispersion 1500-1600rpm.
[0098] In some specific embodiments of the present invention, the order of adding materials in the dry mixing is half the mass of part of the positive electrode active material, the conductive agent and the other half the mass of part of the positive electrode active material.
[0099] The mixed powder is dispersed and wetted with a solvent and kneaded to obtain a slurry mass. The revolution speed of the kneading step is 15 to 20 rpm. The present invention does not specifically limit the type of solvent used to prepare the slurry, and any solvent known to those skilled in the art for preparing battery slurry can be used. In the present invention, NMP is preferably used.
[0100] The dispersant, the solvent and the remaining part of the positive electrode active material are mixed with the slurry mass and stirred. In the present invention, the dispersant is selected from a cationic dispersant, preferably, the cationic dispersant is selected from an amine salt dispersant, and further preferably, the amine salt dispersant is selected from one or more of an alcoholamine dispersant, a quaternary ammonium salt dispersant, and a pyridinium salt dispersant.
[0101] In the present invention, the mass percentage of the cationic dispersant in the high solid content slurry is 0.3% to 0.5%, which can be 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, or any value between 0.3% and 0.5%.
[0102] The mixing and stirring time is 90 to 100 minutes, the speed is 25 to 30 rpm for revolution, 800 to 900 rpm for dispersion, and the temperature is controlled at 44 to 46° C. In the present invention, the mass ratio of part of the positive electrode active material to the remaining part of the positive electrode active material is 50 to 60:40 to 50, which can be 50:50, 55:45, 60:40, or any value between 50 to 60:40 to 50.
[0103] Then, it is mixed with the conductive agent slurry for pre-stirring and high-speed dispersion to obtain a slightly higher viscosity slurry. The pre-stirring time is 10 to 15 minutes, the speed is 15 to 20 rpm for revolution and 500 to 600 rpm for dispersion; the high-speed dispersion time is 60 to 65 minutes, the speed is 30 to 35 rpm for revolution and 3000 to 3500 rpm for dispersion; the present invention has no special restrictions on the conductive slurry, and any conductive slurry known to those skilled in the art can be used. In the present invention, the conductive slurry is preferably a conductive graphite slurry or a carbon nanotube slurry.
[0104] The present invention also mixes a binder with a solvent to obtain a mixed glue solution; in the mixed glue solution, the mass ratio of the binder to the solvent is (5% to 10%): (95% to 90%), which can be any value between 5%: 95%, 7%: 93%, 10%: 90%, or (5% to 10%): (95% to 90%). In the present invention, there is no special restriction on the type of the bonding, and any type of binder known to those skilled in the art can be used. In the present invention, the binder is preferably polyvinylidene fluoride.
[0105] Finally, the slightly high viscosity slurry is mixed with the mixed glue to obtain a high solid content slurry. The mixing includes pre-stirring and high-speed dispersion, the pre-stirring time is 10-15 minutes, the speed is 15-20 rpm for revolution and 500-600 rpm for dispersion; the high-speed dispersion time is 90-100 minutes, the speed is 30-35 rpm for revolution and 3200±10 rpm for dispersion, and the temperature is controlled at 34-36°C.
[0106] In the high solid content slurry, the mass ratio of the positive electrode active material, the binder, the conductive agent and the conductive slurry is (95.8-96.3%): (1.8-2.2%): (0.8-1.2%): (0.7-1.0%).
[0107] In the present invention, since the dispersant can be completely volatilized without any residue, it does not occupy the proportion of the ingredients.
[0108] The present invention also provides a high-solid content slurry prepared by the above preparation method. Depending on the type of slurry, the solid content in the high-solid content slurry provided by the present invention can be increased by 5% to 8%, and the viscosity remains basically consistent with the viscosity of conventional slurry.
[0109] The present invention further provides a lithium ion battery, comprising the above-mentioned high solid content slurry. In the present invention, the lithium ion battery comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is prepared by using the above-mentioned high solid content slurry.
[0110] The slurry prepared by the invention has excellent stability and good performance, and can not only reduce the amount of solvent N-methylpyrrolidone used but also reduce drying energy consumption, save manufacturing costs, and increase the solid content of the slurry.
[0111] In order to further understand the present invention, the high solid content slurry and its preparation method and lithium ion battery provided by the present invention are described below in conjunction with embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0112] In the following examples, the alcohol amine dispersant is purchased from Shanghai Miaoxu New Material Technology Co., Ltd., and is a dispersant of model Voltan 200.
[0113] Example 1
[0114] In this embodiment, the preparation method of the positive electrode slurry with high solid content by semi-dry kneading process (see the process flow chart) Figure 1 ), comprising the following steps (the slurry preparation ratio is LFP: PVDF: SP: CNT = 95.8%: 2.2%: 1.2%: 0.8%, ensuring that the obtained slurry viscosity is about 10000mpa.s):
[0115] (1) The binder polyvinylidene fluoride and the solvent N-methylpyrrolidone are mixed and stirred in a mass ratio of 9:91 to prepare a polyvinylidene fluoride adhesive solution for standby use.
[0116] (2) Conductive carbon black and a certain amount of positive electrode active material are dry-mixed and stirred in a mass ratio of 1:60.1875: the order of adding materials is 1 / 2LFP→SP→1 / 2LFP; the mass of the certain amount of positive electrode active material is 60% of the total mass of the positive electrode active material; the dry mixing and stirring time is 30 minutes, and the speed is: revolution (25±1) rpm, dispersion (1500±10) rpm.
[0117] (3) Add a certain amount of solvent N-methylpyrrolidone (adjust the solid content to about 76%) to uniformly disperse, moisten and knead. The kneading step only involves revolution at a speed of (20±1) rpm.
[0118] (4) Add the remaining amount of positive electrode active material, solvent N-methylpyrrolidone and 0.3% of the total mass of the slurry to wet, and stir at a high solid content (solid content of about 84%): the amount of amine dispersant added is 0.3% of the total amount of the slurry; the stirring time is 90 minutes, the speed is (25±1) rpm for revolution, (800±10) rpm for dispersion, and the temperature is controlled at a low temperature of 44°C and a high temperature of 46°C.
[0119] (5) Add conductive paste (solid content of about 76%) for pre-stirring and high-speed dispersion: the pre-stirring time is 10 minutes, the speed is revolution (15±1) rpm, and the dispersion is (500±10) rpm; the high-speed dispersion time is 60 minutes, the speed is revolution (30±1) rpm, and the dispersion is (3000±10) rpm.
[0120] (6) Add the prepared glue solution (solid content of about 66%) for pre-stirring and high-speed dispersion to obtain a positive electrode slurry with high solid content and appropriate viscosity: the pre-stirring time is 10 minutes, the speed is revolution (15±1) rpm, and the dispersion is (500±10) rpm; the high-speed dispersion time is 90 minutes, the speed is revolution (30±1) rpm, and the dispersion is (3200±10) rpm, and the temperature is controlled at a low temperature of 34°C and a high temperature of 36°C.
[0121] The positive electrode slurry of this embodiment can be used to prepare positive electrode sheets and further to prepare lithium-ion batteries.
[0122] The specific values of the amount of NMP required for preparing the slurry in this example are shown in Table 1.
[0123] Test the change of slurry viscosity over time and record the data. See Table 2 for specific test values.
[0124] The specific test values of the rate performance of the full battery prepared in this embodiment are shown in Table 3.
[0125] Example 2
[0126] In this embodiment, the preparation method of the positive electrode slurry with high solid content by semi-dry kneading process (see the process flow chart) Figure 1 ), comprising the following steps (the slurry preparation ratio is LFP: PVDF: SP: CNT = 95.8%: 2.2%: 1.2%: 0.8%, ensuring that the obtained slurry viscosity is about 10000mpa.s):
[0127] (1) The binder polyvinylidene fluoride and the solvent N-methylpyrrolidone are mixed and stirred in a mass ratio of 9:91 to prepare a polyvinylidene fluoride adhesive solution for standby use.
[0128] (2) Conductive carbon black and a certain amount of positive electrode active material are dry-mixed and stirred in a mass ratio of 1:60.1875: the order of adding materials is 1 / 2LFP→SP→1 / 2LFP; the mass of the certain amount of positive electrode active material is 60% of the total mass of the positive electrode active material; the dry mixing and stirring time is 30 minutes, and the speed is: revolution (25±1) rpm, dispersion (1500±10) rpm.
[0129] (3) Add a certain amount of solvent N-methylpyrrolidone (adjust the solid content to about 76%) to uniformly disperse, moisten and knead. The kneading step only involves revolution at a speed of (15±1) rpm.
[0130] (4) Add the remaining amount of positive electrode active material, solvent N-methylpyrrolidone and alcohol amine dispersant for wetting, and stir at high solid content (solid content of about 84%): the amount of alcohol amine dispersant added is 0.35%, 0.4% and 0.45% of the total amount of the slurry, respectively; the stirring time is 90 minutes, the speed is (25±1) rpm for revolution, (800±10) rpm for dispersion, and the temperature is controlled at a low temperature of 44°C and a high temperature of 46°C.
[0131] (5) Add conductive paste (solid content of about 76%) for pre-stirring and high-speed dispersion: the pre-stirring time is 10 minutes, the speed is revolution (15±1) rpm, and the dispersion is (500±10) rpm; the high-speed dispersion time is 60 minutes, the speed is revolution (30±1) rpm, and the dispersion is (3000±10) rpm.
[0132] (6) Add the prepared glue solution (solid content of about 66%) for pre-stirring and high-speed dispersion to obtain a positive electrode slurry with high solid content and appropriate viscosity: the pre-stirring time is 10 minutes, the speed is revolution (15±1) rpm, and the dispersion is (500±10) rpm; the high-speed dispersion time is 90 minutes, the speed is revolution (30±1) rpm, and the dispersion is (3200±10) rpm, and the temperature is controlled at a low temperature of 34°C and a high temperature of 36°C.
[0133] The positive electrode slurry of this embodiment can be used to prepare positive electrode sheets and further to prepare lithium-ion batteries.
[0134] The viscosity change of the slurry when the amount of the alcohol amine dispersant added was 0.35%, 0.4% and 0.45% of the total amount of the slurry was tested and the data were recorded. The specific test values are shown in Table 1.
[0135] Comparative Example 1
[0136] In this comparative example, the preparation method of the positive electrode slurry by the wet process (see the process flow chart) Figure 2 ), comprising the following steps (the slurry preparation ratio is LFP: PVDF: SP: CNT = 95.8%: 2.2%: 1.2%: 0.8%, ensuring that the obtained slurry viscosity is about 10000mpa.s):
[0137] (1) The binder polyvinylidene fluoride and the solvent N-methylpyrrolidone are mixed and stirred in a mass ratio of 9:91 to prepare a polyvinylidene fluoride adhesive solution.
[0138] (2) Add SP and conductive paste to the prepared glue solution and stir to disperse to form a conductive paste sealed with a binder: stir and disperse at a revolution speed of (25±1) rpm for 30 minutes, then stir at a revolution speed of (30±1) rpm and a dispersion speed of (3000±10) rpm for 120 minutes.
[0139] (3) The positive electrode active material and the solvent N-methylpyrrolidone are mixed in a mass ratio of 3:1 and stirred and added into the solvent for infiltration to obtain a positive electrode active material infiltration solution: stirring and dispersing is first stirred at a revolution speed of (20±1) rpm for 30 minutes, and then stirred at a revolution speed of (30±1) rpm and a dispersion speed of (2000±10) rpm for 100 minutes.
[0140] (4) Add the conductive paste sealed with the binder to the fully moistened positive electrode active material and stir to obtain a uniformly dispersed positive electrode slurry: stir and disperse at a revolution speed of (25±1) rpm for 10 minutes, and then stir at a revolution speed of (30±1) rpm and a dispersion speed of (5000±10) rpm for 90 minutes.
[0141] The positive electrode slurry of this embodiment can be used to prepare positive electrode sheets and further to prepare lithium-ion batteries.
[0142] The specific values of the amount of NMP required for preparing the slurry in this example are shown in Table 1.
[0143] Test the change of slurry viscosity over time and record the data. See Table 2 for specific test values.
[0144] The specific test values of the rate performance of the full battery prepared in this embodiment are shown in Table 3.
[0145] Comparative Example 2
[0146] In this embodiment, the preparation method of the positive electrode slurry with high solid content by semi-dry kneading process (see the process flow chart) Figure 1 ), comprising the following steps (the slurry preparation ratio is LFP: PVDF: SP: CNT = 95.8%: 2.2%: 1.2%: 0.8%, ensuring that the obtained slurry viscosity is about 10000mpa.s):
[0147] (1) The binder polyvinylidene fluoride and the solvent N-methylpyrrolidone are mixed and stirred in a mass ratio of 9:91 to prepare a polyvinylidene fluoride adhesive solution for standby use.
[0148] (2) Conductive carbon black and a certain amount of positive electrode active material are dry-mixed and stirred in a mass ratio of 1:60.1875: the order of adding materials is 1 / 2LFP→SP→1 / 2LFP; the mass of the certain amount of positive electrode active material is 60% of the total mass of the positive electrode active material; the dry mixing and stirring time is 30 minutes, and the speed is: revolution (25±1) rpm, dispersion (1500±10) rpm.
[0149] (3) Add a certain amount of solvent N-methylpyrrolidone (adjust the solid content to about 76%) to uniformly disperse, moisten and knead. The kneading step only involves revolution at a speed of (15±1) rpm.
[0150] (4) Add the remaining amount of positive electrode active material, solvent N-methylpyrrolidone and 0.3% PVP dispersant of the total mass of the slurry for wetting, and stir at high solid content (solid content of about 80%): the amount of PVP dispersant added is 0.3% of the total slurry; the stirring time is 90 minutes, the speed is revolution (25±1) rpm, dispersion (800±10) rpm, and the temperature is controlled at low temperature 44°C and high temperature 46°C.
[0151] (5) Add conductive slurry (solid content of about 71%) for pre-stirring and high-speed dispersion: the pre-stirring time is 10 minutes, the speed is revolution (15±1) rpm, and the dispersion is (500±10) rpm; the high-speed dispersion time is 60 minutes, the speed is revolution (30±1) rpm, and the dispersion is (3000±10) rpm.
[0152] (6) Add the prepared glue solution (solid content of about 62%) for pre-stirring and high-speed dispersion to obtain a positive electrode slurry with high solid content and appropriate viscosity: the pre-stirring time is 10 minutes, the speed is revolution (15±1) rpm, and the dispersion is (500±10) rpm; the high-speed dispersion time is 90 minutes, the speed is revolution (30±1) rpm, and the dispersion is (3200±10) rpm, and the temperature is controlled at a low temperature of 34°C and a high temperature of 36°C.
[0153] The positive electrode slurry of this embodiment can be used to prepare positive electrode sheets and further to prepare lithium-ion batteries.
[0154] The specific values of the amount of NMP required for preparing the slurry in this example are shown in Table 1.
[0155] Test the change of slurry viscosity over time and record the data. See Table 2 for specific test values.
[0156] The specific test values of the rate performance of the full battery prepared in this embodiment are shown in Table 3.
[0157] Test Case
[0158] The viscosity stability test of the positive electrode slurry obtained in Example 1, Comparative Example 1 and Comparative Example 2 is carried out. The test method is: using a conventional viscometer to test the viscosity of the slurry immediately, 1h, and 24h. The test results are shown in Table 2 and Figure 3 .
[0159] The full battery prepared with the positive electrode slurry of Example 1 and Comparative Example 1 was tested at 25°C with a 2C rate discharge platform. The results are shown in Figure 4 .
[0160] The positive electrode slurries obtained in Example 1 and Comparative Example 1 were made into full batteries for electrochemical testing. The test conditions were 25°C and 0.5C / 0.5C charge and discharge cycles were used for testing. The test results are shown in Table 1 and Figure 5 .
[0161] Table 1
[0162]
[0163] Table 2
[0164] Solid content% Instant viscosity map.s 1h viscosity mpa.s 24h viscosity mpa.s Example 1 66 10300 10410 12200 Comparative Example 1 61 10320 10590 14630 Comparative Example 2 62 10310 10490 13000
[0165] Table 3
[0166]
[0167]
[0168] The method for preparing a lithium ion battery slurry with a high solid content by a semi-dry kneading process provided by the present invention does not change the original semi-dry kneading process, but improves the solid content and stability of the positive electrode slurry by properly using a dispersant, reduces production costs, and further enhances the market competitiveness of the battery.
[0169] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a high solid content slurry, characterized in that: The following steps are involved: A) mixing a conductive agent, a positive electrode active material, a dispersant and a solvent to obtain a slightly high viscosity slurry, wherein the dispersant is selected from a cationic dispersant; B) mixing the binder with the solvent to obtain a mixed glue solution; C) mixing the slightly higher viscosity slurry with the mixed glue to obtain a high solid content slurry.
2. A method for preparing a high solid content slurry, characterized in that: The following steps are involved: a) mixing a positive electrode active material, a dispersant and a solvent and then mixing with a conductive agent slurry to obtain a slightly higher viscosity slurry, wherein the dispersant is selected from a cationic dispersant; b) mixing the binder with the solvent to obtain a mixed glue solution; c) mixing the slightly higher viscosity slurry with the mixed glue to obtain a slurry with a high solid content.
3. A method for preparing a high solid content slurry, characterized in that: The following steps are involved: 1) mixing a conductive agent, a positive electrode active material, a dispersant and a solvent and then mixing with a conductive agent slurry to obtain a slightly higher viscosity slurry, wherein the dispersant is selected from a cationic dispersant; 2) mixing the binder and the solvent to obtain a mixed glue solution; 3) Mixing the slightly higher viscosity slurry with the mixed glue to obtain a high solid content slurry.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The mass percentage of the cationic dispersant in the high solid content slurry is 0.3% to 0.5%; The cationic dispersant is selected from amine salt dispersants.
5. The preparation method according to claim 4, characterized in that: The amine salt dispersant is selected from one or more of an alcohol amine dispersant, a quaternary ammonium salt dispersant, and a pyridinium salt dispersant.
6. The preparation method according to any one of claims 1 to 3, characterized in that: Step A) comprises: A1) dry-mixing the conductive agent with part of the positive electrode active material to obtain a mixed powder; Dispersing and wetting the mixed powder with a solvent and kneading them to obtain a slurry mass; A2) mixing the dispersant, the solvent and the remaining positive electrode active material with the slurry mass to obtain a slurry with a slightly higher viscosity; Step a) comprises: a1) dispersing and wetting a portion of the positive electrode active material with a solvent and kneading the mixture to obtain a slurry mass; a2) mixing the dispersant, the solvent and the remaining positive electrode active material with the slurry mass, and then mixing with the conductive agent slurry for pre-stirring and high-speed dispersion to obtain a slurry with slightly higher viscosity; Step 1) includes: 1-1) dry-mixing the conductive agent with part of the positive electrode active material to obtain a mixed powder; Dispersing and wetting the mixed powder with a solvent and kneading them to obtain a slurry mass; 1-2) The dispersant, the solvent and the remaining positive electrode active material are mixed with the slurry mass and stirred, and then mixed with the conductive agent slurry for pre-stirring and high-speed dispersion to obtain a slurry with slightly higher viscosity.
7. The preparation method according to claim 6, characterized in that: In step A1) and step 1-1), the dry mixing time is 30±5 min, and the speed is: revolution 25-30 rpm, dispersion 1500-1600 rpm; In step A1) and step 1-1), the order of adding materials in the dry mixing is half the mass of part of the positive electrode active material, the conductive agent and the other half the mass of part of the positive electrode active material; In step A1), step a1) and step 1-1), the revolution speed of the kneading step is 15 to 20 rpm; In step A2), step a2) and step 1-2), the mixing and stirring time is 90 to 100 minutes, the speed is 25 to 30 rpm for revolution, 800 to 900 rpm for dispersion, and the temperature is controlled at 44 to 46°C; In step a2) and step 1-2), the pre-stirring time is 10 to 15 minutes, the speed is 15 to 20 rpm for revolution and 500 to 600 rpm for dispersion; the high-speed dispersion time is 60 to 65 minutes, the speed is 30 to 35 rpm for revolution and 3000 to 3500 rpm for dispersion; In step C), step c) and step 3), the mixing includes pre-stirring and high-speed dispersion, the pre-stirring time is 10 to 15 minutes, the speed is 15 to 20 rpm for revolution and 500 to 600 rpm for dispersion; the high-speed dispersion time is 90 to 100 minutes, the speed is 30 to 35 rpm for revolution and 3200 ± 10 rpm for dispersion, and the temperature is controlled at 34 to 36°C.
8. The preparation method according to any one of claims 1 to 3, characterized in that: In the mixed glue, the mass ratio of the binder to the solvent is (5% to 10%): (95% to 90%); In the high solid content slurry of step C), the mass ratio of the positive electrode active material, the binder, and the conductive agent is (95.8-96.3%): (1.8-2.2%): (0.8-1.2%); In the high solid content slurry of step c), the mass ratio of the positive electrode active material, the binder and the conductive slurry is (95.8-96.3%): (1.8-2.2%): (0.7-1.0%); In the high solid content slurry of step 3), the mass ratio of the positive electrode active material, the binder, the conductive agent and the conductive slurry is (95.8-96.3%): (1.8-2.2%): (0.8-1.2%): (0.7-1.0%); In step A1), step a1) and step 1-1), the mass ratio of part of the positive electrode active material to the remaining part of the positive electrode active material is 50-60:40-50.
9. A high solid content slurry prepared by the preparation method according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: Comprising the high solid content slurry as described in claim 9.
Citation Information
Patent Citations
Preparation method of battery slurry with high solid content
CN107834019A